Effect of Product Quality, Service and Price on Consumer Satisfaction (Case Study on Warung Tengah Sawah Restaurant Business) - Akhmad Nasir; Achmad Nur Fuad Chalimi (International Journal of Integrative Research, 2023)
In this research, service and price are partially and together on consumer satisfaction. With product iquality, iservice iand iprice ias independent ivariables iand icustomer satisfaction ias ithe idependent ivariable. iThe type iof iresearch iused iwas iquantitative, ithe population iin ithis istudy iwere icustomers iwho had ieaten iat ithe iWarung iTengah iSawah Restaurant iwith ia isample iof i55 ipeople. iData analysis iused iis iMultiple iLinear iRegression, instrument test and classical assumption test. The results of the research on product quality have a t-count value of 2.625 (sig. 0.019 <0.05) service has a t-count value of 2.114 (sig. 0.052> 0.05) prices have a t-count value of 0.256 (sig. 0.612>0.05) which indicates that product quality partially ihas ia isignificant ieffect ion icustomer satisfaction, iwhile iservice iand iprice ipartially have ian iinsignificant ieffect ion icustomer satisfaction. iAs iwell ias itogether ithe iquality of products, services and prices have a significant effect on customer satisfaction. Evidenced by the large F count of 5.492 with a sig. F (0.006 <0.05).